Treatability Studies on the Optimization of Ozone and Carbon Dosages for the Effective Removal of Contaminants from Secondary Treated Effluent - P. Ganesh Kumar; S. Kanmani; P. Senthil Kumar (Adsorption Science & Technology)
This study investigates the novel and advanced integrated pilot-scale treatment system of removal of contaminants in the secondary effluent from municipal wastewater. The main intent of this work is to assess the combination of pressure sand filter (PSF), ultrafiltration (UF), ozone (O3), and granular activated carbon (GAC) to treat wastewater and evaluate its suitability for water reuse. The experiments were carried out in a following condition: PSF+UF+O3+GAC, PSF+O3+GAC, and PSF+UF+GAC. Configuration 1 was found to be more effective when compared to the other two and almost there occurred complete removal of contaminants. Whereas configuration 2 had the lowest removal efficiency of all, and configuration 3 had quite positive results. The influence of process parameters such as ozone dosage, flow rate, and filtration time was optimized. The optimized filtration time was 20 min with the filtration feed flow rate of 300 LPH. The best configuration of this treatment process produced a removal efficiency of about 80 to 90% with the ozone dosage of 8.33 mg/L with a flow rate of 4 l/min, whereas there occurred complete removal by the subsequent action of GAC. Moreover, the biodegradability of wastewaters as measured by the BOD5/COD ratio increased from 0.45 to 0.53. The proposed integrated pilot-scale process was effective in removing contaminants to the required level of discharge in the environment or reuse and it will pave the way to provide significant benefits to wastewater treatment.